The Terminal Segment of the Seminiferous Tubule: The Current Discovery of Its Morphofunctional Importance in Mammals - Seco-Rovira, Vicente; Beltrán-Frutos, Ester; Martínez-Hernández, Jesús; Madrid, Juan Francisco; Pastor, Luis Miguel (Cells (Basel, Switzerland), 2025)
The morphophysiology of intratesticular sperm pathways in mammals, including humans, is poorly understood. The seminiferous tubule is continuous with the straight tubule; however, its final portion—the terminal segment (TS)—has a different tissue composition. This paper reviews the most important histological results from mammal studies from the last decades of the 20th century, including the different nomenclatures given to the TS. The TS presents a loss of spermatogenesis and is lined mainly with modified Sertoli cells. There is no unanimity among authors when it comes to naming and defining TS. In the last ten years, studies on rats and mice have highlighted the importance of this testicular zone, proposing that there is a high proliferation of modified Sertoli cells with an undifferentiated cellular profile associated with stem spermatogonia. In hamsters, an immunohistochemical study showed the existence of heterogeneity between these cells, and the surrounding interstitium presents numerous Leydig cells that are ultrastructurally different from those of the rest of the testis rest. In conclusion, we have only just begun to understand the tissue biology of TS. Emerging research is very promising; it can potentially modify our current knowledge of testicular biology and be very useful in promoting the advancement of male fertility restoration therapies in andrology.